PREVALENCE OF GENITAL TRACT PROBLEMS IN CLINICAL CASES OF VARIOUS SPECIES OF ANIMALS - A. Z. Durrani; N. Kamal (Journal of Animal and Plant Sciences, 2009)
The prevalence of reproductive disorders in various animals including buffaloes, cattle, sheep , goats and mares was estimated from the record of Civil Veterinary Hospital , Jia Bagga, district Lahore for the period from January 2004 to December 2007. A total of 1216 cases of obstetrical problems, female reproductive tract infections, reported anoestrus, repeat breeding and vaginal bleeding were recorded. In buffalo prevalence of retention of foetal membranes (22.8%0), followed by vaginal/uterine prolapse (22.5%), anoestrus (19.9%), uterine infection (12.7%), dystochia (9.8%), torsion of the uterus (7.2%), abortion (3.3%), vaginal infection (1.1%) and repeat breeding (0.7%) was recorded. In cattle corresponding values were 30.6, 19.4, 12.9, 12.9, 11.3, 8.1, 3.2 and 1.6% respectively. In goats prevalence of45.8% was recorded for dystochia followed by abortions (23.0%), retention of foetal membranes (10.6%),uterine infection (9.3%), vaginal /uterine prolapse (3.6%), reported anoestrus (2.3%), vaginal infection (2.1%) ,vaginal bleeding (1.7%).In sheep corresponding values were 52.6,8.0,5.3,0.38,23.7,0.38,0.38 and 0.38% respectively. In mare highest prevalence (34.0%) was recordedfor reported anoestrus followed by abortions (31.8%), uterine infection (15.9%), vaginal infection (11.4%) and dystochia, retention of placenta, prolapse (1.43%).
Keywords: Reproductive problems; animals. Pakistan; Punjab